Effect of mechanical damage under repeated loading and abrasion on the tensile behaviour of a reinforcement geocomposite. Issue 1 (1st October 2022) - Carneiro, J R; Carvalho, F; Almeida, F; de Lurdes Lopes, M
Abstract: The installation process and the occurrence of abrasion may cause unwanted changes on the properties of the geosynthetics. When identified as relevant degradation agents for a given application, their effect has to be properly taken into account during the design phase in order to guarantee that the geosynthetics will perform correctly their functions over time. In this work, a reinforcement geocomposite (formed by a nonwoven polypropylene geotextile reinforced with polyethylene terephthalate filaments) was exposed to the isolated and combined effects of two degradation tests: mechanical damage under repeated loading and abrasion (the geocomposite was tested on both sides, which were structurally different). Damage assessment was performed by visual inspection and tensile tests. Based on the changes occurred in tensile strength, reduction factors were determined. The degradation tests provoked extensive damage on the geocomposite, having a negative impact on its tensile behaviour. Contrary to mechanical damage under repeated loading, the effect of abrasion on the geocomposite was influenced by the side that was tested. Finally, some differences were found between the reduction factors determined by the traditional method (multiplication of reduction factors obtained in isolation for each agent) for the combined effect of mechanical damage under repeated loading and abrasion and those resulting from the successive exposure to both degradation agents.